2016
DOI: 10.1055/s-0036-1571336
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Embolism As a Consequence of Ultrasonographic Examination of Extremities for Suspected Venous Thrombosis: A Systematic Review

Abstract: Ultrasonographic examination for deep vein thrombosis (DVT) appears to be a safe diagnostic method, but a theoretical concern has been raised for dislodgment of thrombi during examination. We conducted a systematic review of the literature to identify reports of possible or confirmed pulmonary embolism (PE) as a consequence of ultrasonographic assessment of extremities in patients with suspected DVT. We searched PubMed for studies published in English from January 1, 1960, to April 10, 2015. We included all co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Similar reports showed that the compression maneuver during ultrasound examination could be one of the contributory factors of thrombus dislodgment. Furthermore, free-floating thrombi or thrombi with free-floating tail in the right lower limb veins might have higher tendency for embolization ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar reports showed that the compression maneuver during ultrasound examination could be one of the contributory factors of thrombus dislodgment. Furthermore, free-floating thrombi or thrombi with free-floating tail in the right lower limb veins might have higher tendency for embolization ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Systematic identification of safety events are challenging, with concern for missing relevant cases due to lack of reporting to regulatory bodies or the published literature or suboptimal indexing. 3,8 It is for this reason that even prior systematic reviews had missed several relevant cases. 3,9 This study had some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Once a thrombus is located, it is prudent to avoid repeat compression or investigation of the area. Although rare, case reports have proposed the association of venous ultrasound with embolic events, and this should be considered in any patient that develops cardiopulmonary symptoms during or after a positive examination 6 …”
Section: Techniquementioning
confidence: 99%